2022
DOI: 10.3390/ijerph19127051
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Serum Biomarkers of Coal Workers’ Pneumoconiosis by Metabolomics Combined with Machine Learning Strategy

Abstract: Pneumoconiosis remains one of the most serious global occupational diseases. However, effective treatments are lacking, and early detection is crucial for disease prevention. This study aimed to explore serum biomarkers of occupational coal workers’ pneumoconiosis (CWP) by high-throughput metabolomics, combining with machine learning strategy for precision screening. A case–control study was conducted in Beijing, China, involving 150 pneumoconiosis patients with different stages and 120 healthy controls. Metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Because the disease is progressive and incurable, early diagnosis or early prevention is especially important to control this disease. Previous studies showed elevated levels of serum markers such as IL-6, IL-8, propylparaben, TGF-β1 in patients with pneumoconiosis [7][8][9] and indicated the potential role of serum biomarkers for the early diagnosis. However, although these biomarkers show promise, they have not yet been applied in clinical settings.…”
Section: Introductionmentioning
confidence: 98%
“…Because the disease is progressive and incurable, early diagnosis or early prevention is especially important to control this disease. Previous studies showed elevated levels of serum markers such as IL-6, IL-8, propylparaben, TGF-β1 in patients with pneumoconiosis [7][8][9] and indicated the potential role of serum biomarkers for the early diagnosis. However, although these biomarkers show promise, they have not yet been applied in clinical settings.…”
Section: Introductionmentioning
confidence: 98%
“…However, no currently available clinical indicator or system can provide sufficiently accurate predictions for disease progression in CWP patients of the early phase 16 . Therefore, developing and validating sensitive and specific clinical indicators to effectively predict the progression of CWP in the early phase is essential.…”
Section: Introductionmentioning
confidence: 99%
“…However, no currently available clinical indicator or system can provide sufficiently accurate predictions for disease progression in CWP patients of the early phase. 16 Therefore, developing and validating sensitive and specific clinical indicators to effectively predict the progression of CWP in the early phase is essential. The objective of this research was the development of a computational tool for predicting the risk of CWP with early stage in dust–exposed workers from large amounts of clinical indicators, which have shown that there were differences between patients confirmed CWP and dust–exposed workers, including arterial blood gas analysis, pulmonary function test, blood cell analysis, inflammatory markers, blood biochemical parameters, coagulation function, and serum tumor markers.…”
Section: Introductionmentioning
confidence: 99%